Evaluating PjBL Instruction with Linguistic Landscape in English Course using CIPP Model - I G. A. P. N. S. Paragae (Indonesian Journal of Foreign Language Studies, 2025)
The lack of resources on the utilization of linguistic landscape (LL) in PjBL (PjBL) leaves educators with problems in its implementation. This evaluative study filled the gap by investigating the implementation of PjBL with LL by making use of CIPP (context, input, process, and product) model with a qualitative approach. Questionnaires and interviews were used to collect the data from 2 lecturers and 44 university students from Tourism Department joining an English course. The study revealed that (1) the learning goals covered four language skills and 21st-century learning skills; (2) the lesson plan, lecturers’ capability, students’ characteristics and ability as well as the facilities were considered sufficient; (3) although students responded positively on the instruction, some problems were faced by lecturers and students, and (4) the instruction resulted in improved students’ language skills and 21st-century skills. The study also produced feedback for more effective and better implementation.